#### Answer

$g(5)-g(-2)=-21$

#### Work Step by Step

We are given:
$g(t)=1-t^{2}$
We evaluate:
$g(-2)=1-(-2)^{2}=1-4=-3$
$g(5)=1-5^{2}=1-25=-24$
$g(5)-g(-2)=-24--3=-24+3=-21$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$g(5)-g(-2)=-21$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.